Reliability testing and heat transfer enhancement of organic phase change materials / Ravi Kumar Sharma - Ravi Kumar, Sharma (2016)
The design and development of a thermal energy storage device require discrete selection of the appropriate phase change material (PCM) and a suitable container to contain them. This study focuses on the selection of PCMs for solar thermal energy storage devices and the improvement in their thermophysical properties. In addition, a new shape of the PCM container is also investigated using computational fluid dynamics. The accelerated thermal cycle test is an essential requirement to ensure the thermal and chemical stability of selected PCMs to be used in practical applications. Solar energy being an unlimited natural energy source is used in a large number of applications such as solar water/air heating, cooking, drying and other domestic and commercial applications. On the other hand, this energy also has limitations as this is available only in the daytime. Storage of this abundantly available solar energy can be effectively used in the night hours or when there are no sunny days. Four organic PCMs-paraffin wax, palmitic acid, myristic acid, and polyethylene glycol (PEG) 6000, all in the melting temperature range of 50-70 ˚C, have been considered in this study and the changes in their thermal and chemical properties have been measured using the differential scanning calorimetry and the Fourier transform infrared techniques. The results of this research work revealed that the changes in the melting temperature of paraffin wax, palmitic acid, myristic acid, and PEG 6000 were in the range of +0.72 ˚C to +3.27 ˚C, -0.29 ˚C to +1.76 ˚C, -2 ˚C to +1.2 ˚C, and 3.77 to 3.94 ˚C respectively. The variation in the latent heat of fusion was found in the range of -9.8 to 14%, 3.28 to 18%, 0.9 to 10%, and 13 to 25 % for paraffin wax, palmitic acid, myristic acid, and PEG 6000 respectively. iv The low thermal conductivity of organic PCMs is a well-known drawback which limits their use in many domestic and industrial applications. A composite of palmitic acid and nano titanium dioxide (TiO2) was prepared and its phase change behavior was investigated. TiO2 nanoparticles of 0.5%, 1.0%, 3.0%, and 5.0% were dispersed into palmitic acid and the thermophysical properties of these nano composites were measured. The composite PCMs were characterized by FESEM, XRD, and FT-IR. The thermal properties, thermal stability and thermal reliability were ensured by DSC, TGA, and thermal cycle testing. FESEM images show the uniform dispersion of nanoparticles in the palmitic acid and FT-IR spectrum indicate that the composite PCM possesses good chemical stability and interaction between PCM and nanoparticles. The results of a thermal conductivity test show that the dispersion of the 5% nanoparticles enhances the thermal conductivity of palmitic acid by 80%. Finally, a novel trapezoidal cavity is proposed for containing the PCM and a detailed parametric study was carried out using two nano enhanced PCMs, paraffin-Cu and water-Cu based on the computational study. The effect of side wall inclination angle, cold wall temperature, nanofluid’s initial temperature, cavity inclination, Grashof number on the total solidification time of nanofluid was simulated. The total solidification time for different wt% of Cu nanoparticles was also investigated in the trapezoidal cavity. The enthalpy–porosity technique is used to trace the solid–liquid interface. The inclination angle can be used efficiently to control the solidification time. In addition, the average Nusselt number along the hot wall for different angles, nanoparticles volume fractions, and Grashof number are presented graphically. The proposed predictions are very helpful in developing an improved latent heat thermal energy storage for the solar heat collector and for casting and mold design.